2010
DOI: 10.1186/1755-1536-3-15
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal cell survival in airway and interstitial pulmonary fibrosis

Abstract: Fibrotic reactions in the airways of the lung or the pulmonary interstitium are a common pathologic outcome after exposure to a wide variety of toxic agents, including metals, particles or fibers. The survival of mesenchymal cells (fibroblasts and myofibroblasts) is a key factor in determining whether a fibroproliferative response that occurs after toxic injury to the lung will ultimately resolve or progress to a pathologic state. Several polypeptide growth factors, including members of the platelet-derived gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(130 citation statements)
references
References 114 publications
3
126
0
1
Order By: Relevance
“…MSC were treated in vitro with bleomycin or TGF-␤1 and analyzed changes in gene expression indicative of myofibroblast transition. TGF-␤1 was chosen because it is a known regulator of fibrosis in many adult tissues as well as in response to bleomycin injury (11,64,71,73). TGF-␤1 target genes were also upregulated in the MSC during the inflammatory phase of bleomycin injury (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSC were treated in vitro with bleomycin or TGF-␤1 and analyzed changes in gene expression indicative of myofibroblast transition. TGF-␤1 was chosen because it is a known regulator of fibrosis in many adult tissues as well as in response to bleomycin injury (11,64,71,73). TGF-␤1 target genes were also upregulated in the MSC during the inflammatory phase of bleomycin injury (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, these results demonstrated that lung MSC protect lung integrity following injury and when endogenous MSC are lost due to abnormal differentiation, their protective function is compromised. In addition to their reparative properties, several studies indicate that lung MSC can instead mediate pathogenic changes within the lung (11,80). Indeed, the behavior of MSC is highly sensitive to the microenvironment to which these cells are exposed (100).…”
Section: Abcg2mentioning
confidence: 99%
“…NiNPs are used as a catalyst in the fabrication of MWCNTs, and there are concerns that they could be a contributing factor to pulmonary fibrosis or mesothelioma (5,6,12). We have previously reported a significant fibrotic response in the lungs and pleura of mice after inhalation exposure to MWCNTs containing residual Ni (8,32).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PDGF production by macrophages can be increased in a hypoxic environment stimulated by exposure to Ni (10,11). PDGF acts as a stimulant of fibroblast growth and chemotaxis through the activation of the mitogen-activated protein kinases (MAPKs) termed extracellular signal-regulated kinase (ERK) -1 and -2 (collectively referred to as ERK), and plays a major role in fibroblast survival (10,12). Fibroblasts are critical to fibrogenesis, as they differentiate into myofibroblasts in response to transforming growth factor (TGF)-b1 to produce collagen, which defines fibrotic lesions (10).…”
mentioning
confidence: 99%
“…In support of this, we have shown that functional blocking antibodies to PDGFR promote adipogenesis and adiponectin secretion when used at concentrations that suppress cell proliferation and PDGF-induced Akt activation similar to that achieved with imatinib. We therefore hypothesise that, in cultures treated with physiological levels of glucocorticoid alone, the basal adipogenic response to glucocorticoid is suppressed by PDGF, which is present in bovine serum, and is secreted in an autocrine and/or paracrine fashion by MSCs (Bonner 2010). Addition of imatinib or functional blocking antibodies ameliorates this inhibitory effect allowing differentiation to proceed unabated.…”
Section: Imatinib Promotes Adipogenesis S Fitter and Others 235mentioning
confidence: 99%